Comparative study between fixed-time artificial insemination and natural mating on reproductive performance (conception and pregnancy rates) of Mpwapwa breed cows in Tanzania : a thesis presented in partial fulfillment of the requirement for the degree of Master of Science in Animal Science, Institute of Veterinary, Animal and Biomedical Sciences, Massey University, Palmerston North, New Zealand - Kabuni, Kabuni Thomas (Massey University, 2017)
The aim of this project was to assess whether using a PGF2α synchronization protocol in Mpwapwa cattle would improve reproductive performance. A standard 14-day PGF2α synchronization protocol with a single FTAI was compared to NM over a 12-weeks breeding season. At the end of the study, 39/100 cows were pregnant in the FTAI group and 49/100 cows were pregnant in the NM group. This difference was not statistically significant (P=0.21), although the odds ratio of pregnancy was lower in the FTAI group than the NM group (unadjusted RR=0.8; 95% - CI 0.58-1.09). However, cattle in the PGF2α-treated group were only inseminated once, whereas the NM group could be naturally mated on multiple occasions during the breeding season; In addition, the use of PGF2α allowed the use of AI, which is not feasible under most Tanzanian systems when cattle come into oestrus naturally. Thus, the results of this study suggest that PGF2α -based synchronization and FTAI, particularly if used alongside natural mating, can improve the reproductive performance of Mpwapwa breed cattle as well as allowing for greater genetic gain than occurs with naturally mated cattle. The proportion of cows that came into heat and displayed behavioural signs after administration of the first PGF2α injection was very low (only 10/100 cattle). The reason for this poor response is unclear. It could be that oestrus detection was not very effective, or that a higher than expected proportion of cattle did not have a responsive CL. The most likely cause of the latter is a higher proportion of cattle in anoestrus. Further investigation of the reproductive state of Mpwapwa cattle at the start of the breeding season would identify how important anoestrus is as a cause of poor reproductive performance. If anoestrus is common, identifying cattle in anoestrus at the start of the season could be useful, as they could be treated using progesterone-based programmes and cattle with a CL could be treated with PGF2α. Key words: Mpwapwa breed cattle, PGF2α synchronization protocol, FTAI, NM, Reproductive performance.
Keywords: Cattle; Reproduction; Artificial insemination; Tanzania; Mpwapwa breed cattle; PGF₂α synchronisation protocol; FTAI; NM; Reproductive performance; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Animal production::Animal breeding